Foraminoplasty at the Tip or Base of the Superior Articular Process for Lateral Recess Stenosis in Percutaneous Endoscopic Lumbar Discectomy: A Multicenter, Retrospective, Controlled Study with 2-Year Follow-Up. (19th December 2018) - Yang, Jun-Song; Chu, Lei; Chen, Chien-Min; Wang, Xiang-Fu; Xie, Pei-Gen; Deng, Rui; Yu, Ke-Xiao; Shi, Lei; Zhang, Zhen-Xing; Rong, Li-Min; Hao, Ding-Jun; Deng, Zhong-Liang
Abstract : Objective . To compare the clinical efficacy and complications which obtained foraminoplasty at the tip or base of the superior articular process (SAP) for the patients with lateral recess stenosis treated by percutaneous endoscopic lumbar discectomy (PELD). Methods . Between January 2015 and January 2016, 156 patients of lumbar disc herniation accompanying with lateral recess stenosis were treated with PELD in five tertiary hospitals and fulfilled the 2-year follow-up. Among them, 78 patients obtained a foraminoplasty at the tip of SAP (group A), and foraminoplasty at the base of SAP was performed in the other 78 cases (group B). Clinical efficacy was evaluated using the visual analog scale (VAS) score for back and leg pain, Oswestry Disability Index (ODI), and 36-item Short-Form Health Survey (SF-36) score. The intervals of follow-up were scheduled at 1 month, 3 months, 6 months, 1 year, and 2 years after surgery. Results . Mean operative duration is shorter in group B (55 versus 61 min, P = 0.047). Only one case belonged to group A could not tolerate the neural irritation and required conversion to an open procedure. During the surgery, no dura tears, cauda equina syndrome, or infections were observed. 5 patients experienced transient dysesthesia located at the exiting nerve in group A, while no cases complained dysesthesia in group B. 2 cases who suffered temporary motor weakness all belonged to group A. A total of 5 cases obtained a revision surgery after recurrence in the follow-up, in which 3 patients belonged to group A. Compared to the preoperative data, significant improvements in VAS scores of low back pain and sciatica, ODI, and SF-36 PCS and MC were observed in the follow-up, respectively (P < 0.05, respectively). However, no statistical difference was observed at all time-points after surgery between these two groups (P > 0.05, respectively). Conclusions . For the patients of LDH accompanying with lateral recess stenosis, compared with the routine foraminoplasty at the tip of SAP, our modified foraminoplastic technique does not only change place of foraminoplasty to the base of SAP but also simplified puncture process in transforaminal PELD. Although there was no significant difference in symptom relief, the modified foraminoplasty showed the advantages in decreasing the incidence of postoperative neural dysfunction and reducing operation time.